Establishing a Swine Model of Acute Respiratory Distress Syndrome Secondary to Ischemia-Reperfusion Injury Following Acute Limb Ischemia - Grzegorz Jodlowski; Rebecca Treffalls; May Dvir; Silvana N Wilken; Jonathan J Morrison; Patrick F Walker (Journal of Endovascular Resuscitation and Trauma Management)
Background: Acute Respiratory Distress Syndrome (ARDS) is a severe complication of ischemia-reperfusion injury (IRI), characterized by acute hypoxemic respiratory failure and high mortality. Acute limb ischemia (ALI) can trigger systemic inflammation leading to ARDS. This study introduces a swine model of ARDS secondary to ALI. Methods: Two Yorkshire swine were used in this study. Animals were anesthetized and subjected to nine hours of hindlimb ischemia via arterial occlusion. The limb was then reperfused and animals monitored through physiological parameters, computed tomography imaging, lung ultrasounds and histology. Data was then analyzed using GraphPad Prism and Analyze software for statistical and imaging evaluation. Results: Baseline measurements confirmed normal vasculature and stability, access was obtained and occlusion delivered. Following nine hours of hindlimb ischemia, reperfusion led to progressive respiratory decline, with worsening oxygenation, decline in the Horowitz index, elevated lactate and potassium levels, and imaging showing early signs of lung injury. Post-mortem analysis confirmed lung congestion, consistent with ARDS. Conclusions: The study demonstrates a novel, easily performed, cost-effective and replicable swine model of ARDS using hindlimb IRI. This model mimics physiological and sterile conditions seen in a clinical setting and serves as a valuable tool for studying ARDS. It also allows for investigation of the systemic inflammatory cascade triggered by peripheral ischemia, mirroring human ARDS cases that occur with distal injuries. Future studies with larger sample sizes and extended critical care periods are recommended to validate the technique and enhance its relevance for experimental applications.